2016
DOI: 10.1155/2016/2794096
|View full text |Cite
|
Sign up to set email alerts
|

Myoinositol Attenuates the Cell Loss and Biochemical Changes Induced by Kainic Acid Status Epilepticus

Abstract: Identification of compounds preventing or modifying the biochemical changes that underlie the epileptogenesis process and understanding the mechanism of their action are of great importance. We have previously shown that myoinositol (MI) daily treatment for 28 days prevents certain biochemical changes that are triggered by kainic acid (KA) induced status epilepticus (SE). However in these studies we have not detected any effects of MI on the first day after SE. In the present study we broadened our research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Equal volume aliquots, containing 30 μ g protein, were applied to the sodium dodecyl sulphate (SDS) gels and electrophoresis and Western blotting were carried out as described previously [ 12 ]. After the protein had been transferred onto nitrocellulose membranes, the membranes were stained with Ponceau S solution and analyzed with Image J software ( https://imagej.net/ImageJ ) to confirm uniform gel loading and transfer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Equal volume aliquots, containing 30 μ g protein, were applied to the sodium dodecyl sulphate (SDS) gels and electrophoresis and Western blotting were carried out as described previously [ 12 ]. After the protein had been transferred onto nitrocellulose membranes, the membranes were stained with Ponceau S solution and analyzed with Image J software ( https://imagej.net/ImageJ ) to confirm uniform gel loading and transfer.…”
Section: Methodsmentioning
confidence: 99%
“…After the protein had been transferred onto nitrocellulose membranes, the membranes were stained with Ponceau S solution and analyzed with Image J software ( https://imagej.net/ImageJ ) to confirm uniform gel loading and transfer. Standard immunochemical procedures were carried out using primary antibodies against HMGB1 (Abcam, ab18256) and peroxidase-labelled secondary antibodies and Super-Signal West Pico Chemiluminescent substrate (Pierce) [ 12 ]. The optical densities of bands, corresponding to the HMGB1 were measured using Lab Works 4.0 (UVP).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we showed neuronal cell loss observed 24 h after KA induced SE in the hippocampus, and MI treatment had a protective effect on cell death [19]. Here we have analyzed whether KA and MI treatment effects in the hippocampus was still observed 8 weeks after SE.…”
Section: Cell Countsmentioning
confidence: 86%